2014
DOI: 10.1016/j.neuropsychologia.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the FFA: The role of the ventral anterior temporal lobes in face processing

Abstract: Extensive research has supported the existence of a specialized face-processing network that is distinct from the visual processing areas used for general object recognition. The majority of this work has been aimed at characterizing the response properties of the fusiform face area (FFA) and the occipital face area (OFA), which together are thought to constitute the core network of brain areas responsible for facial identification. Although accruing evidence has shown that face-selective patches in the ventra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
134
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 191 publications
(149 citation statements)
references
References 212 publications
(362 reference statements)
15
134
0
Order By: Relevance
“…This suggests that the anterior FG plays a role in person identification and memory. This hypothesis is consistent with fMRI and brain lesions studies showing that anterior temporal lobe may play a role in face individualization and semantic knowledge about people (e.g., Busigny et al, 2014a;Joubert et al, 2006;Kriegeskorte, Formisano, Sorger, & Goebel, 2007;Nestor, Plaut, & Behrmann, 2011;Von Der Heide, Skipper, & Olson; for reviews see Collins & Olson, 2014, Gainotti, 2007Gobbini & Haxby, 2007;Olson, Plotzker, & Ezzyat, 2007). However, these studies rarely investigated the role of the anterior FG specifically.…”
Section: What Is the Role Of The Right Anterior Fg In Face Processing?supporting
confidence: 81%
See 1 more Smart Citation
“…This suggests that the anterior FG plays a role in person identification and memory. This hypothesis is consistent with fMRI and brain lesions studies showing that anterior temporal lobe may play a role in face individualization and semantic knowledge about people (e.g., Busigny et al, 2014a;Joubert et al, 2006;Kriegeskorte, Formisano, Sorger, & Goebel, 2007;Nestor, Plaut, & Behrmann, 2011;Von Der Heide, Skipper, & Olson; for reviews see Collins & Olson, 2014, Gainotti, 2007Gobbini & Haxby, 2007;Olson, Plotzker, & Ezzyat, 2007). However, these studies rarely investigated the role of the anterior FG specifically.…”
Section: What Is the Role Of The Right Anterior Fg In Face Processing?supporting
confidence: 81%
“…Most recently, fMRI studies have also reported ventral face-selective regions anterior to the FFA, up to the temporal pole (e.g., Avidan et al, 2014;Nasr & Tootell, 2012;Rajimehr, Young, & Tootell, 2009;Rossion, Hanseeuw, & Dricot, 2012;; for a recent review, see Collins & Olson, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although patients with brain lesions or atrophy to the anterior temporal lobe may have difficulties recognising known individuals, this impairment may reflect a loss of semantic knowledge about people, rather than a primarily visual deficit (Ellis, Young, & Critchley, 1989;Gainotti, 2013;Gainotti, Barbier, & Marra, 2003). However, more recent evidence favours the view that the anterior temporal lobe is also linked to visual-perceptual stages of face processing (for a review, see Collins & Olson, 2014).…”
Section: The Neural Architecture Of the Face Processing Systemmentioning
confidence: 99%
“…Here, we tested the hypothesis that a region in the anterior temporal lobe (ATL) has a function akin to a person identity node (1,9,10), subserving access to abstract person identity representations that can be retrieved from multiple cues, such as when you see a photo of Graceland and it cues your knowledge of Elvis (study 1). Next, we asked whether the ATL acts as a neural switchboard, performing in concert with other brain regions to enable the retrieval of different facets of person knowledge in a flexible and context-appropriate manner (study 2).…”
mentioning
confidence: 99%
“…Individuals with ATL damage due to resection or stroke have multimodal person recognition deficits (34), lose access to stored knowledge about familiar people (35,36), and have difficulties learning information about new people (4,22,37,38). A subregion of the ATL contains a face-sensitive patch, first identified in monkeys, and more recently in humans (9).…”
mentioning
confidence: 99%